2008
DOI: 10.1039/b802871k
|View full text |Cite
|
Sign up to set email alerts
|

Systematic approach to new ligands for anion recognition based on ureido-calix[4]arenes

Abstract: Mono,arenes in the cone, partial cone and 1,3-alternate conformations have been synthesised and their complexation ability towards selected anions has been studied. The structure-anion complexation ability relationship has been systematically monitored. A new type of very efficient ligands based on diureido-calix [4]arene in a 1,3-alternate conformation with pronounced bonding ability towards carboxylates was designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 47 publications
4
30
0
Order By: Relevance
“…752 These studies led to the conclusion that neither cone nor partial cone conformations displayed a preference for dihydrogenphosphate over other anions in deuterated chloroform:acetonitrile (4:1). At the same time, receptors 742b and 742d with 1,3-alternate conformations were found to exhibit slightly greater affinities for dihydrogenphosphate as compared to other anions under these conditions (e.g., K (H 2 PO 4 - ) = 3.2 × 10 3 M -1 and K (PhCO 2 - ) = 2.1 × 10 3 M -1 for receptor 742b ).…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…752 These studies led to the conclusion that neither cone nor partial cone conformations displayed a preference for dihydrogenphosphate over other anions in deuterated chloroform:acetonitrile (4:1). At the same time, receptors 742b and 742d with 1,3-alternate conformations were found to exhibit slightly greater affinities for dihydrogenphosphate as compared to other anions under these conditions (e.g., K (H 2 PO 4 - ) = 3.2 × 10 3 M -1 and K (PhCO 2 - ) = 2.1 × 10 3 M -1 for receptor 742b ).…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…These groups provide strong and directional hydrogen bonds generating deeply preorganized receptors. Examples of calix[4]‐(thio)ureido‐based anion receptors have been reported, as well as examples of ureidocalix[5]arenes and calix[6]arenes , . Ditopic receptors, simultaneously binding both anion and cation of a given ion pair, may display higher affinity and selectivity compared to simple ion receptors, due to a cooperative binding process.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Calix [4]arenes bearing one or more (thio)urea groups on either the lower or the upper rim, have been the most studied for anion recognition. [7][8][9][10][11] Ureidocalix [5]arene 12 and calix [6]arene 13 derivatives have also been tested as anion receptors. Along with calixarene's development, dihomooxacalix [4]arenes (calix [4]arene analogues in which one CH 2 bridge is replaced by one CH 2 OCH 2 group), 14 have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has previously led to consistent values and to predict site reactive effects in agreement with experiments. [35][36][37] Only selected values associated to the urea moieties were used because, as mentioned above, this region is the reactive site for the binding process ( The results showed that the highest value correspond to the ∑ ߱ ା ሺሻ for the fragment containing the phenyl residue (10), which suggests that this site is the more prone for charge acceptance during the hydrogen bonding process, compared to the other ureas. Furthermore, the calculated data for this residue is significantly different from those for compounds 7-9, opposite to the previously described behavior of the global criteria ω + ( Table 3).…”
Section: Introductionmentioning
confidence: 99%